Presentation and Outcome of Surgical Management of Strangulated Inguinal Hernia at Liaquat University Hospital Hyderabad (Medical Forum Monthly, 2024)
Aim: The objectives of the study are to determine the incidence of strangulated inguinal hernia in patients presenting with irreducibility and obstruction, evaluate the age and sex incidence, see the duration of hospital stay in our setup and see the post operative morbidity and mortality. Study Design: Experimental Study. Place and Duration of Study: This study was carried out in Surgical Unit-IV, Liaquat University Hospital Jamshoro, from 2007 to 2009. Materials and Methods: 100 cases of obstructed hernia were selected out of which 85 with strangulation were included in this study. These patients were admitted through the outpatient department, as well as from casualty department of Liaquat University Hospital Jamshoro/Hyderabad. All these patients were admitted in emergency. Results were prepared with help of tables and graphs. Data was analyzed through SPSS software . Results: 140 patients presenting with obstructed hernia were selected of which 85 were found to have strangulated hernia. There was wide variation of age ranging from a minimum 15 to 70 years with the mean age 42 years. 55 patients had Right sided hernia 64.7% and 30 patients had Left sided hernia 35.2% and no patient with bilateral strangulated inguinal hernia reported 0%. During surgery of 60 patients (70.5%) had gangrenous omentum while 23 cases (27%) ileum was non viable so we had to resort to resection and anastmosis, two cases (2.3%) Ileum was so much contaminated so we had to resort to Ileostomy and two case (2.3%) sigmoid colon was involved so we had to resort to colostomy. Postoperatively majority of them developed wound infection 14 (16.4%) followed by chest infections 10 (11.7%) Haematoma formation was reported in 5 (5.8%) and retention of urine in 3 patient (3.5%). Conclusion: Good pre-operation assessment and early management will decrease the morbidity and mortality in strangulated inguinal hernia.